Alterações histopatológicas e expressão de citocinas e de fatores angiogênicos em placenta de gestantes portadoras de pré-eclâmpsia - Weel, Ingrid Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Preeclampsia (PE) is a specific syndrome of human pregnancy, characterized by the onset of hypertension and proteinuria after the 20th week of gestation. It is accepted that this disease originates in the placenta, probably due to factors involved in its formation and development. The objectives of the present study were: 1) To evaluate the histopathology of placental lesions in pregnant women with PE and in normotensive pregnant women; 2) To compare the frequency of newborns with intrauterine growth restriction among the groups of pregnant women studied. One hundred and forty pregnant women were evaluated, of whom 20 were normotensive and 120 were preeclamptic. Pregnant women with PE were classified according to the appearance of clinical manifestations in early-onset PE (<34 weeks of gestation - n = 40) and late-onset PE (≥ 34 weeks gestation - n = 80). A fragment of placenta was obtained immediately after delivery and prepared for histopathological analysis. Placental sections of 4m were placed on a slide for hematoxylin - eosin (HE) staining. Histological examination of placentas showed that the most frequently alterations found in patients with PE were increase villous with syncytial knots, infarction, increased fibrin deposits and distal villi hypoplasia. Placenta of pregnant women with early-onset PE showed higher percentage of villous with syncytial knots for gestation age compared with late-onset PE and normotensive pregnant women. Infarct and distal villi hypoplasia were more frequent in placenta of pregnant women with PE, whereas fibrin deposits were significantly increased in women with early-onset PE than in late-onset PE. Moreover, the percentage of newborns with intrauterine growth restriction was higher (37.8%) in patients with early–onset PE than in late-onset PE (14.3%). Together the results show that pregnant women with early-onset PE showed placentas with higher percentage of lesions and newborns with ...

A pré-eclâmpsia (PE) é uma síndrome específica da gestação humana, caracterizada pelo aparecimento de hipertensão arterial e proteinúria após a 20ª. semana de gestação. É aceito que esta patologia tem origem na placenta, provavelmente em decorrência de fatores envolvidos na sua formação e desenvolvimento. O presente projeto teve como objetivo: 1) Avaliar comparativamente a histopatologia de lesões placentárias em gestantes portadoras de PE e gestantes normotensas; 2) Comparar a frequência de recém-nascidos com restrição de crescimento intrauterino entre os grupos de gestantes estudados. Foram avaliadas 140 gestantes, sendo 20 normotensas e 120 com PE. As gestantes com PE foram classificadas de acordo com o aparecimento das manifestações clínicas em PE precoce (< 34 semanas de gestação - n=40) e PE tardia (≥ 34 semanas de gestação – n= 80). Um fragmento de placenta foi obtido imediatamente após o parto e preparado para análise histopatológica, sendo os cortes histológicos de 4m de espessura colocados sobre lâmina histológica para coloração pelo método de Hematoxilina - Eosina (HE). O exame histológico das placentas mostrou que as patologias mais frequentemente encontradas em gestantes com PE foram aumento de vilos com nós sinciciais, infarto, aumento de depósito de fibrina e hipoplasia de vilos distais. Placentas de gestantes portadoras de PE precoce apresentaram maior percentagem de vilos com aumento de nós sinciciais para a idade gestacional em comparação a gestantes normotensas e com PE tardia. O infarto placentário e a hipoplasia de vilos distais foram mais frequentes em gestantes portadoras de PE quando comparadas às normotensas, enquanto o depósito de fibrina foi maior em gestantes com PE precoce do que nas com PE tardia. Além disso, a percentagem de recém-nascidos com restrição de crescimento intrauterino foi significativamente maior (37,8%) em gestantes com PE precose ...
Keywords: Pre-eclampsia; Placenta; Citocinas; Neovascularização; Histopatologia; Utero - Crescimento; Gravidez - Complicações; Cytokines